Genetics of rough seed coat texture in cowpea - Singh, B.B.; Ishiyaku, M. (2000)
Seed coat texture is an important trait in determining the acceptability of cowpea varieties in different regions. A rough seed coat is preferred in western and central Africa, since it permits easy removal of the seed coat which is essential for indigenous food preparations. On the other hand, a smooth seed coat is preferred in eastern and southern Africa as well as in parts of South America where cowpea is consumed as boiled beans without removing the seed coats. This study was undertaken to elucidate the inheritance of seed coat texture so that cowpea breeders may adopt appropriate breeding strategy to develop cowpea varieties with preferred seed types for different regions. The F1 plants between smooth- and rough-seeded parents as well as between rough- and rough-seeded parents produced smooth seeds, indicating a complementary gene action and dominance for smooth seed coat. The F2 plants from the smooth x rough cross segregated into a 3 smooth:1 rough seed coat ratio, but the F2 plants from rough x rough crosses segregated into a 9 smooth:7 rough seed coat ratio. The F1 plants from backcross to the smooth parent were all smooth, while the F1 plants from backcross to rough parent segregated in a 1 smooth:1 rough seed coat ratio. However, both the backcross populations in rough x rough crosses segregated into 1 smooth:1 rough seed coat ratio. These results indicate that two pairs of independent recessive genes confer rough seed coat texture in cowpea and the presence of at least one dominant gene at each of the two loci results into smooth seed coat. The gene symbols rt1rt1 and rt2rt2 are being assigned for rough seed coat texture in cowpea.